Older Adults' Narratives of Seeking Mental Health Treatment: Making Sense of Mental Health Challenges and "Muddling Through" to Care. (August 2020) - Reynolds, Kristin; Medved, Maria; Mackenzie, Corey S.; Funk, Laura Megan; Koven, Lesley
Older adults who experience challenges related to mental health are unlikely to seek professional help. The voices of older adults who have navigated through mental health issues and systems of care to arrive at psychological treatment are less well understood. We conducted individual interviews with 15 adults aged 61 to 86 who sought psychological treatment. Interviews were audio-recorded, transcribed, and analyzed using narrative methods. We identified several main storylines that describe the meaning-making and treatment-seeking journeys of older adults: resistance to being labeled with mental health problems (telling stories of resistance, defining mental health issues in mysterious and uncontrollable terms, and experiencing internal role conflict); muddling through the help-seeking process (manifestations of chaos and system-level barriers); and emotional reactions to psychological treatment (hope, fear, and mistrust). Findings add to the literature base in the area of narrative gerontology, and highlight the complex experiences that older adults face when seeking psychological treatment.